2020
DOI: 10.14748/vmf.v9i2.7360
|View full text |Cite
|
Sign up to set email alerts
|

Application of chlorhexidine in endodontics

Abstract: За да се постигне оптимален резултат от ендодонтското лечение, бактериалните популации в кореновия канал трябва да бъдат елиминирани или наймалкото да бъдат значително редуцирани до нива, съвместими с оздравителния процес на периапикалните тъкани. Иригационните разтвори играят важна роля за отстраняването на заразената тъкан, бактериите и техните продукти на разпадане, а също така влияят върху разграждането на органичната и неорганичната материя в системата на кореновите канали. Медикаментите, които в момента … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Contrary to these conclusions, Tonea A. et al [18] found in their study that calcium hydroxide showed very low efficacy against Candida albicans and Enterococcus faecalis and should not be used alone as an antimicrobial agent. Supporters of this theory are other authors (Zancan R. F. 2016) [19], who prove the need for the combination of calcium hydroxide with chlorhexidine to control microbial infection, confirmed in another study [20].…”
Section: Discussionmentioning
confidence: 75%
“…Contrary to these conclusions, Tonea A. et al [18] found in their study that calcium hydroxide showed very low efficacy against Candida albicans and Enterococcus faecalis and should not be used alone as an antimicrobial agent. Supporters of this theory are other authors (Zancan R. F. 2016) [19], who prove the need for the combination of calcium hydroxide with chlorhexidine to control microbial infection, confirmed in another study [20].…”
Section: Discussionmentioning
confidence: 75%